1933
DOI: 10.6028/jres.010.008
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of ultra-violet solar radiation in various localities

Abstract: In the present paper a description is given of the calibration of a selective photochemical, ultra-violet dosage intensity meter against a balanced thermocouple and filter radiometer, used as a standard. Data are given of the ultra-violet intensities of solar radiation in various localities at various elevations at various stations in Europe and upon the ocean.The measurements show a high ultra-violet reflection from clean fresh snow. The ultra-violet intensities over the ocean are not conspicuously higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1933
1933
1950
1950

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The present measurements substantiate the earlier data (5) showing that the greater susceptibility to sunburn at the seashore is not explainable exclusively on the basis of an excessively higher ultraviolet radiation than obtains at the same level inland; but that skin sensitization by sea water, and increased penetrability of the rays into the moist skin must also be considered.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The present measurements substantiate the earlier data (5) showing that the greater susceptibility to sunburn at the seashore is not explainable exclusively on the basis of an excessively higher ultraviolet radiation than obtains at the same level inland; but that skin sensitization by sea water, and increased penetrability of the rays into the moist skin must also be considered.…”
supporting
confidence: 90%
“…This question was discussed in an earlier paper (5) in which it was shown that the ultraviolet radiation intensities observed over the ocean were not conspicuously higher than at a sea-level station, situated inland, at the same latitude and at the same season of the year. R ecently, in connection with the other radiometric work at San Juan, P. R., an opportunity was presented to verify these earlier measurements, using greater refinements in making the observations.…”
Section: -35---4 146 Journal Of Research Of the National Bureau Ofmentioning
confidence: 97%
“…Concerning the Stefan-Boltzmann constant of total radiation, the value (o-= 5.70X 10~1 2 watt/cm 2 /deg. 4 ) used in that calibration is a trifle lower than more recent estimates (o-= 5.71 to 5.75) of this constant (9) in which corrections have been made for atmospheric absorption.…”
Section: Establishment Of the Reference Standards Of Thermal Radiationmentioning
confidence: 80%
“…In view of the difficulties in making direct radiometric measurements in absolute value, the original carbon-filament lamp standards of radiation of the Bureau were obtained by direct comparison with a black body (at 1,000°to 1,150°C), the radiant flux of which was calculated on the assumption that the Stefan-Boltzmann constant of total radiation is o-= 5.7X 10 -12 watt/cm 2 /deg. 4 (2) (9).…”
Section: Establishment Of the Reference Standards Of Thermal Radiationmentioning
confidence: 99%
“…The compounds selected for this work were the ones reported to absorb most effectively that part of the sun's spectrum which has maximal erythemal efficiency (4). All solutions were made up to 0.001 % in absolute alcohol except tannic acid which was dissolved in distilled water.…”
Section: Methodsmentioning
confidence: 99%